PROBLEMS AND SOLUTIONS FOR AUTOMATING ORTHOEPIC NORMS IN THE UZBEK LANGUAGE (Scientific journal of the Fergana State University, 2026)
This article provides a scientific and practical analysis of the challenges involved in automating orthoepic norms in the Uzbek language and proposes possible solutions. The study highlights the importance of automating orthoepic standards for the development of speech culture, particularly for improving the quality of text-to-speech (TTS) systems. Key challenges such as dialectal diversity, exceptions to orthoepic norms, and the lack of annotated orthoepic corpora are identified. To address these issues, the article proposes the standardization of dialectal speech and the development of comprehensive orthoepic corpora.